Encouraging writers: introduction to the scope of the scientific journal "Musiktherapeutische Umschau". Issue 1 (1st June 2016) - Bernius, Volker; Bergmann, Thomas; Körber, Annegret; Scheytt, Nicola; Smetana, Monika; Sonntag, Jan
Abstract : Background : The editors of the German scientific journal "Musiktherapeutische Umschau" (MU) invite authors, potential authors, reviewers and editors of other journals as well as the interested readership to gather information about the publishing policy and the scope of the MU. Objective : Generally, we aim to encourage interested scientists and practitioners to publish their own research articles and practical reports/case studies to make them accessible to the music therapy community. Methods : Presentations, practical work in small groups, discussions. Results : Participants will find answers to the following questions: Which publication formats are accepted? What are the requirements for different publication formats (e.g. original work, document)? What does the process from submitting a manuscript to receiving the printed article look like? What does a "peer review process" entail? What can I do to improve my manuscript and increase its chances of getting published? Conclusions : Research needs a vision; writing is a mission! Note : The workshop will be German.